PERAN GURU DALAM MEMBANGUN KARAKTER MANDIRI PADA SISWA KELAS V SD AL - KHAIRIYYAH MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA PELAJARAN IPAS - Rukhma, Akrabatu; Widiana Rahayu, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers in fostering independent character among fifth-grade students through the implementation of Project Based Learning (PjBL) in IPAS subjects at SD Al-Khairiyyah Surabaya. The study is based on the problem that students’ independence has not been optimally developed due to teacher-centered learning practices. This research employed a descriptive qualitative approach. Data were collected through classroom observations, interviews, and documentation. Data analysis used the interactive model of Miles and Huberman. The findings indicate that the implementation of PjBL contributes to the development of students’ self-confidence, responsibility, discipline, and problem-solving skills. However, the formation of independent character is strongly influenced by the teacher’s role in managing student autonomy in a structured and consistent manner throughout the learning process. Keywords: Project Based Learning, independent character, teacher’s role,IPAS learning, elementary school